Development of tourism objects with ADO-ODTWA, IFE, EFE at Muara Indah Beach Kota Agung, Tanggamus - Efendi, Edi; Efendi, Nur; Kaskoyo, Hari; Rochana, Erna; Damai, Abdullah Aman (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2025)
The attraction of a tourist attraction must have its own uniqueness and development strategy compared to other tourist attractions. The research aims to identify types of tourism; analyze tourist attractions with ADO-ODTWA; and develop strategies for the development of tourist areas through IFE and EFE Analysis with a SWOT matrix approach at Muara Indah Beach. The research was conducted from November to December 2024 at Muara Indah Beach, Tanggamus Regency. Data collection techniques are carried out by observation, questionnaires, interviews, and literature studies. The types of tourist attractions at Muara Indah Beach are divided into types of nature tourism, cultural tourism, and sports tourism. The results of the ADO-ODTWA assessment obtained The results of the assessment show that the variables of Attraction of Tourism Objects and Service Management fall into the “Not Feasible” category; variables of Accessibility, Conditions Around the Area, Supporting Facilities and Infrastructure, and Availability of Clean Water, fall into the “Feasible” Category. The results of the entire assessment of the ADO-ODTWA variable Muara Indah Beach are in the “Good to Develop (B)” category. The development strategy found that the IFE and EFE analysis is in the Grow and Develop position.  Internal Factors and External Factors found that the score results are >2. The most important strategy to be carried out at Muara Indah Beach is the SO (Streght Opportunity) Strategy. SO strategies (1) build partnerships with relevant agencies; (2) maximize tourism opportunities; and (3) increase the number of visitors to the beach.